Copper Shaft-Hole Axes and Early Metallurgy in South-Eastern Europe - Heeb, Julia (Archaeopress, 2014)
Although the copper axes with central shaft-hole from south-eastern Europe have a long history of research, they have not been studied on a transnational basis since the 1960s. What has also been missing, is trying to use as many methods as possible to better understand their production, use and context.